Comparison between Conventional Breath-hold and Respiratory-triggered Magnetic Resonance Cholangiopancreatography with and without Compressed Sensing: Cross-sectional Study - Kim, Younguk; Lee, Eun Sun; Park, Hyun Jeong; Park, Sung Bin; Kuehn, Bernd; Sung, Jae Kon; Lim, Yaeji; Kim, Changwoo (Current Medical Imaging, 2024)
Introduction The application of compressed sensing (CS) has enabled breath-hold 3D-MRCP with a shorter acquisition time in clinical practice. Aim To compare the image quality of breath-hold (BH) and respiratory-triggered (RT) 3D-MRCP with or without CS application in the same study population. Methods In this retrospective study, from February to July 2020, a total of 98 consecutive patients underwent four different acquisition types of 3D-MRCP.; 1) BH MRCP with the generalized autocalibrating partially parallel acquisition (GRAPPA) (BH-GRAPPA), 2) RT-GRAPPA-MRCP, 3) RT-CS-MRCP and 4) BH-CS-MRCP. Relative contrast of common bile duct, 5-scale visibility score of biliary pancreatic ducts, 3-scale artifact score and 5-scale overall image quality score were evaluated by two abdominal radiologists. Results Relative contrast value was significantly higher in BH-CS or RT-CS than in RT-GRAPPA (0.90 ± 0.057 and 0.89 ± 0.079, respectively, vs. 0.82 ± 0.071, p < 0.01) or BH-GRAPPA (vs. 0.77 ± 0.080, p < 0.01). The area affected by artifact was significantly lower in BH-CS among 4 MRCPs (p < 0.01). Overall image quality score in BH-CS was significantly higher than BH-GRAPPA (3.40 vs. 2.71, p < 0.01). There were no significant differences between RT-GRAPPA and BH-CS (vs. 3.13, p = 0.67) in overall image quality. Conclusion In this study, our results revealed BH-CS had higher relative contrast and comparable or superior image quality among four MRCP sequences.
Keywords: Data compression